2005
DOI: 10.1227/01.neu.0000180960.75347.11
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of 168 Bilateral Subthalamic Nucleus Implantations by Means of the Probabilistic Functional Atlas

Abstract: PFA-based planning may be superior to the current practice of using anatomic atlases that provide delineation of the target structure only, because it is more precise and provides a unique target point in the stereotactic space. This best stereotactic target is the point in the individualized atlas with the highest probability, meaning the highest probability of having the best target on the basis of the patients previously operated on. This best target is located in the hot STN, the size of which determines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 17 publications
5
54
0
2
Order By: Relevance
“…While our patient-specific model system suffers from a number of limitations, the comparisons with our clinical measurements are consistent with previous studies on location of therapeutically effective electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). The results of this study, though limited to a single patient, suggest that the therapeutic volume of tissue to activate is centered on ZI/H2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…While our patient-specific model system suffers from a number of limitations, the comparisons with our clinical measurements are consistent with previous studies on location of therapeutically effective electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). The results of this study, though limited to a single patient, suggest that the therapeutic volume of tissue to activate is centered on ZI/H2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…These studies have resulted in general guidelines on the selection of stimulation parameters, as well as clinical algorithms for programming the devices. Imaging studies have developed correlations between stimulation parameters and markers of brain activity (Hershey et al, 2003;Haslinger et al, 2005;Phillips et al, 2006;Trost et al, 2006), and identified the location of therapeutic DBS electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). Modeling studies have characterized the theoretical effects of DBS electric fields on the underlying neural tissue (McIntyre et al, 2004b;Miocinovic et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations